Differences in the detection of circulating Hsp90 alpha between patients with atopic dermatitis and dermatitis herpetiformis - Sitko, Krzysztof; Kárpáti, Sarolta; Węgrzyn, Grzegorz; Mincewicz, Grzegorz; Trzeciak, Magdalena; Kasperkiewicz, Michael; Tukaj, Stefan (Frontiers in Medicine, 2024)
Hsp90α is one of the key intra-and extracellular chaperones responsible for the biological activity of various signaling molecules that are involved in (auto)immune-mediated inflammatory diseases. Recent epidemiologic data suggests that patients with atopic dermatitis (AD) are at risk for several autoimmune diseases including dermatitis herpetiformis (DH), an extraintestinal manifestation of celiac disease (CD). In addition, pruritic diseases such as AD may be confused clinically with DH. Here, we aimed to determine the role of circulating Hsp90α in patients with AD in relation to patients with DH, CD, and healthy controls. Using an enzyme-linked immunosorbent assay, levels of circulating Hsp90α were determined in serum samples derived from patients with AD (n=31), DH (n=26), and CD (n=15), as well as and healthy controls (n=55). Although serum concentrations of Hsp90α were similar between patients with DH, CD, and healthy controls, we found that serum levels of Hsp90α were significantly higher (5.08-fold; p < 0.0001) in patients with AD when compared to patients with DH. A cut-off value calculated as 2 x standard deviation above the mean concentration of Hsp90α in DH patients revealed that 83.9% (26/31) of AD patients were Hsp90α positive, whereas none of the DH patients (0/26) displayed such a positivity. This preliminary study suggests a distinct role for extracellular Hsp90α in the pathogenesis of AD compared to DH and its potential use in distinguishing AD from DH. Nevertheless, the role of the evaluation of extracellular Hsp90α for distinguishing between AD and DH is at present speculative and requires further study.